Development of new geopolymers based on stone cutting waste. (10th October 2020) - Simão, L.; Hotza, D.; Ribeiro, M.J.; Novais, R.M.; Montedo, O.R.K.; Raupp-Pereira, F.
Highlights: Stone cutting waste (SW) was used in metakaolin-based geopolymers. SW introduction affected porosity and composition. Interaction between MK and SW promoted an increase in compressive strength. SW-based geopolymer obtained can be used in different applications; Abstract: The use of calcium-rich materials in geopolymerization has been reported in the literature and generally induces an increase in mechanical properties. In this work, stone cutting waste (SW) was used in new geopolymers formulations and the interaction of the components was evaluated. In addition to the filler effect, SW affected the compositional system producing different geopolymer gels when compared to the formulation containing only metakaolin. The samples with 50 and 75 wt% SW achieved a compressive strength of ~28 and ~14 MPa, respectively. In conclusion, SW is a promising raw material for geopolymers, whose properties suggest distinct applications.